Pathologies of Recognition: Axel Honneth and the Renewed Possibility of a Critical Theory of Society - Hazeldine, Gary (Sociologija. Mintis ir veiksmas, 2017)
This article is a critical engagement with the work of Axel Honneth and his significance for contemporary Critical Theory, social explanation, and emancipatory politics. I begin by exploring Honneth’s sympathies for, and criticisms of, both first generation critical theory and Jürgen Habermas’s emphasis on communicative action. I then consider Honneth’s turn to Hegel’s early work on recognition and his emphasis on the underlying forms of mutual recognition, along with the accompanying forms of self-relation/realisation, disrespect and the potential for moral development and resistance. I explore these alongside Honneth’s ‘formal conception of ethical life’ which he hopes can successfully mediate between formal Kantian morality and substantive communitarian ethics whilst also providing him with both a philosophical justification for his normative position and a standard of moral development for evaluating forms of, and struggles for, recognition. I also briefly outline his recent work on reification and recognition before then considering a number of critical responses to Honneth’s project as a whole. Whilst sympathetic to his focus on recognition, my criticisms of his work emphasise his tendency to idealise the notion of recognition, his lack of a sufficient conception of misrecognition, the ideological role that recognition often plays, and ultimately the abstract and procedural nature of his ‘formal’ conception of ethical life.